Answer:
The age of the person now is 16 years old
Explanation:
Let us solve the question
Assume that the age of the person now is x years old
∵ The age of the person now is x years old
∵ His age 10 years ago = x - 10
∵ His age 10 years after = x + 10
∵ The product of his ages 10 years ago and 10 years after is 156
→ Multiply his ages before and after and equate the product by 156
∴ (x - 10)(x + 10) = 156
∵ (x - 10)(x + 10) = (x)(x) + (x)(10) + (-10)(x) + (-10)(10)
∴ (x - 10)(x + 10) = x² + 10x - 10x - 100
→ Add the like terms
∴ (x - 10)(x + 10) = x² + (10x - 10x) - 100
∴ (x - 10)(x + 10) = x² - 100
→ Substitute it in the equation above
∵ x² - 100 = 156
→ Add 100 to both sides
∴ x² - 100 + 100 = 156 + 100
∴ x² = 256
→ Take √ for both sides
∴ √x² = √256
∴ x = 16
∵ x represents his age now
∴ The age of the person now is 16 years old